Exploring Relations between Beliefs about the Genetic Etiology of Virtue and the Endorsement of Parenting Practices. (3rd April 2021) - Rivera, Grace N.; Vess, Matthew; Brooker, Rebecca J.; Stichter, Matt; Neiderhiser, Jenae M.
SYNOPSIS: Objective. We investigated associations between adults' beliefs about the heritability of virtue and endorsements of the efficacy of specific parenting styles. Design. In Studies 1 ( N = 405) and 2 ( N = 400), beliefs about both the genetic etiology of virtuous characteristics and parenting were assessed in samples of parents and non-parents. In Study 3 ( N = 775), participants were induced to view virtue as determined by genes or as determined by social factors. Heritability beliefs and authoritarian parenting endorsements were subsequently measured. Results. Study 1 and Study 2 converged to reveal that tendencies to view characteristics as determined by genes were positively associated with endorsement of authoritarian parenting styles. This association occurred independent of individual differences in essentialism and right-wing authoritarianism. Study 3 revealed that exposure to genetic accounts of virtue increased beliefs that virtue is caused by genes, which in turn was positively associated with endorsements of authoritarian parenting responses to child problem behavior. Exposure to genetic accounts of virtue increased endorsement of authoritarian parenting among parents, but was unrelated to authoritarian parenting among non-parents. Conclusions. These studies suggest that genetic accounts of virtuous characteristics reliably relate to more positive beliefs about harsh and controlling parenting practices, illuminating an unrecognized cognitive factor associated with authoritarian parenting endorsement.